Moderating Factors and Customer Loyalty of Selected Hotels in Lagos State, Nigeria - K. A, Ladipo Patrick; Solomon A, Agada; Salome, Ighomereho O (Journal of Asian Business Strategy, 2020)
The moderating variable has the tendency of increasing or decreasing the strength of the relationship between the independent and dependent variables. However, factors that moderate this relationship have scarcely been research upon in the hotel services sector. This study therefore examined the moderating effects of five salient demographic variables (sex, age, education, occupation, income) on the relationship between customer satisfaction and loyalty. The study employed descriptive research design with cross-sectional survey using a structured questionnaire to collect the data. The data were analysed using percentages and General Linear Model (GLM). The results show that age, education, and occupation significantly moderate the relationship between customer satisfaction and loyalty while sex and income do not at the 0.05 significant level. Based on the findings of this, it is therefore recommended that hotel managers should consider the significant effect of age, educational qualification, and occupation in determining the extent of the relationship between customer satisfaction and loyalty when formulating and implementing marketing strategies.